2014
DOI: 10.1093/hmg/ddu359
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 is a master regulator of insulin production and processing

Abstract: Genome-wide association studies have revealed >60 loci associated with type 2 diabetes (T2D), but the underlying causal variants and functional mechanisms remain largely elusive. Although variants in TCF7L2 confer the strongest risk of T2D among common variants by presumed effects on islet function, the molecular mechanisms are not yet well understood. Using RNA-sequencing, we have identified a TCF7L2-regulated transcriptional network responsible for its effect on insulin secretion in rodent and human pancreat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 78 publications
8
121
1
2
Order By: Relevance
“…Another predicted target is TCF7L2, whose polymorphisms have been correlated to type 2 diabetes mellitus (T2DM). [31] Functional down-regulation of this protein via miR-938 could induce dysregulation of glucose homeostasis. Similarly, dysregulation of circulating miR-126-3p has been reported as a marker for impaired glucose intolerance and new-onset T2DM.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Another predicted target is TCF7L2, whose polymorphisms have been correlated to type 2 diabetes mellitus (T2DM). [31] Functional down-regulation of this protein via miR-938 could induce dysregulation of glucose homeostasis. Similarly, dysregulation of circulating miR-126-3p has been reported as a marker for impaired glucose intolerance and new-onset T2DM.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Having established that CART affects expression of insulin and genes crucial for insulin secretion and processing, we next examined expression of the transcription factors known to regulate these genes (Melloul et al, 2002;Zhou et al, 2014;Fu et al, 2013). CART KD resulted in decreased expression of Tcf7l2, Mafa, Isl-1, Pdx-1, NeuroD1, Nkx2.2 and Nkx6.1 mRNA to 51.4 ± 3.7%, 39 ± 7.9%, 50.5 ± 4.3%, 61.7 ± 2.5%, 56.9 ± 5.9%, 65.1 ± 4.8%, and 79.7 ± 6.5% respectively (p < 0.001 and p < 0.05 for Nkx6.1, Fig.…”
Section: Silencing Of Cart In Ins-1 (832/13) Cells Represses Key Betamentioning
confidence: 99%
“…Furthermore, it was recently shown that TCF7L2, through binding to ISL-1, regulates proinsulin production and processing via e.g. MAFA, PDX-1 and PCSK2 (Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study [19] has shown that TCF7L2 has 17 exons, of which five are alternative splicing. Genetic variants of gene are associated with increased risk of Type 2 Diabetes [20,21]. The prevalence of Type 2 Diabetes shows wide ethnic and geographic variations.…”
Section: Tcf7l2 Gene Polymorphism In T2dm With Patients In Turkish Pomentioning
confidence: 99%